Health promotion through collaborative health: a Tuscan model. (20th October 2021) - Erba, F; Moscatelli, C; Agostinelli, V; Iavazzo, F; Ingeborg, U; Trapè, P; Bellucci, S; D'Amato, G; Dei, S; Doretti, V
Abstract: Background: chronic diseases affect in Italy about 39.1% of the total population and 85.3% of the over 75 years. A new experimental approach has been studied that, through the communities, activate collaborative processes to improve the health and well-being of population. The ASL Toscana Sudest for the three years 2017-2020 has acquired from the Self-management Resource Center (SMRC, University of Stanford California) licenses for implementing self-management programs for chronically ill people. The training process is subject to quality control by SMRC with annual report. Objectives: the goal is to train participants in the solution of problems, to make decisions, to set objectives and define priorities, to undertake actions for clinical-emotional management and its social role. The self-management education processes carried out have been addressed primarily to the diabetes program. Results: 57 conductors were trained through the administration of 30 hours of frontal lessons to nurses and lay people. Subsequently, the conductors implemented 77 programs in which a total of 750 people participated. Of these, 90% took part in at least four of the six seminars provided for in the program. In addition, a specific program has been launched for a group of 13 Bengali citizens resident in Italy with particular attention to the risk of development of dysmetabolic diseases and the possible correlation with Ramadan. Conclusions: the engagement of the citizen in terms of Public Health manifests itself with a cumulative impact of small behavioral changes at the level of individuals, communities, and the population. Main message: the project aims to introduce the concept of 'Collaborative Health' offering concrete examples of experiences already present in the Tuscan context, formulating possible recommendations for stakeholders for the innovation of the system and stimulating greater sustainability, appropriateness and equity of services and health models in Italy. Key messages: Collaborative health is a winning strategy for health promotion. Chronic diseases are a main topic for health promotion.